Mixotrophic Cultivation of Dunaliella tertiolecta in Cheese Whey Effluents to Enhance Biomass and Exopolysaccharides (EPS) Production: Biochemical and Functional Insights - Konstantina Tsotsouli; Spyros Didos; Konstantinos Koukaras; Anagnostis Argiriou (Marine Drugs)
The rapid growth of the dairy industry has resulted in a significant increase in the generation of effluents, which are characterized by a high organic content that poses environmental challenges. In alignment with sustainable practices and the principles of the circular economy, this study investigates the valorization of cheese whey (CW) effluents through the cultivation of the microalga Dunaliella tertiolecta under mixotrophic conditions. The research aims to utilize cheese whey effluents as a supplemental growth medium to enhance the production of algal biomass and extracellular polymeric substances (EPSs). The results reveal that CW facilitated a 37% improvement in D. tertiolecta growth and led to an approximately eight times greater biomass productivity compared to under photoautotrophic conditions, while the EPS production increased by 30%. Chemical and techno-functional analyses of the microalgal biomass and EPSs suggest promising applications as natural product additives for the food industry. Biomass derived from photoautotrophic culture demonstrated greater antioxidant activity and total polyphenols content. Additionally, the lipid profile revealed 16 distinct fatty acids. On the other hand, biomass from the mixotrophic culture exhibited higher protein levels and eight fatty acids, indicating the influence of the cultivation mode on the biochemical composition. Regarding the EPSs, mixotrophic cultivation resulted in elevated antioxidant activity and total polyphenols content, as well as higher protein and sugar levels. Furthermore, the EPSs produced under mixotrophic conditions exhibited superior techno-functional properties compared to those of the photoautotrophic culture, making them ideal candidates for use as alternative natural food additives.